WEB-QUEST AS MODERN METHODS OF TEACHING A FOREIGN LANGUAGE IN A NON-LINGUISTIC UNIVERSITIES (Uzbek Scholar Journal, 2022)
This article discusses the educational web-quest as one of the new educational technologies. The article presents its role and use at different levels of learning a foreign language. The article also describes the description and functions of a web quest in teaching a foreign language in a non-linguistic university. The article reveals the methods of teaching a foreign language in a non-linguistic universities and its contribution to improving efficiency.